A PZT high frequency ceramic surface metallization method

By preparing the Fe2AlB2 transition layer on the PZT high-frequency ceramic surface and depositing the Ag and/or Cu metallization layer, the problem of insufficient firmness of the metallization layer in the prior art is solved, and the bonding strength and the performance of electronic components are significantly improved.

CN119263892BActive Publication Date: 2025-02-14HUNAN MEICHENG NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411816521.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-14
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

In the prior art, the firmness of the metallization layer on the piezoelectric ceramic surface is poor, resulting in limited service life and performance of electronic components.

Method used

Using a PZT high-frequency ceramic surface metallization method, the Fe2AlB2 transition layer is prepared on the ceramic surface and the Ag and/or Cu metallization layer are prepared on the surface, and the metallization layer is deposited by magnetron sputtering method.

Benefits of technology

This method effectively improves the bonding strength between the metallization layer and PZT high-frequency ceramics, alleviates the thermal stress problems caused by differences in material properties, and significantly improves the firmness of the metallization layer and the performance of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263892B_ABST
    Figure CN119263892B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of ceramic metallization, in particular to a method for metallizing the surface of a PZT high-frequency ceramic. The method comprises the following steps: firstly preparing a PZT high-frequency ceramic; preparing a ternary transition metal boride transition layer on the surface of the PZT high-frequency ceramic; and finally preparing a metallization layer on the surface of the ternary transition metal boride transition layer. In the present application, the ternary transition metal boride transition layer is in the transition region from a typical metal to a typical ceramic, and its performance is also between the two, which effectively bridges the property gap between metals and ceramics, can effectively promote the bonding between the PZT high-frequency ceramic and the metallization layer, and effectively alleviate the thermal stress caused near the interface due to the large difference in the properties of the two materials, thereby improving the bonding strength between the metallization layer and the PZT high-frequency ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic metallization, in particular to a PZT high-frequency ceramic surface metallization method. Background Art

[0002] PZT series ceramics are an important type of piezoelectric ceramics, which are widely used in various electronic components. The metallization of the piezoelectric ceramic surface directly affects the service life and performance of electronic components.

[0003] At present, the process of metallization treatment of piezoelectric ceramic surface is based on screen printing or vacuum coating. The screen printing method is to directly print the silver electrode slurry on the surface of the piezoelectric ceramic substrate by screen printing, and then prepare it into a metallization layer through processes such as drying and silver burning. The vacuum coating method is a physical process in which the required metal block is placed in the sagger of the vacuum coating machine, and the metal is heated and melted by electricity in the sagger, and then evaporated. After contacting the piezoelectric ceramic substrate, it is deposited on the surface of the substrate to form a metallization layer. However, due to the difference in the properties of piezoelectric ceramics and metals, the screen printing method or vacuum coating method has certain defects, and the firmness of the prepared metallization layer is poor. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a method for metallizing the surface of PZT high-frequency ceramics.

[0005] The technical solutions adopted are as follows:

[0006] A PZT high-frequency ceramic surface metallization method, as follows:

[0007] First, prepare PZT high-frequency ceramics;

[0008] Fe is prepared on the surface of the PZT high frequency ceramic 2 AB 2 transition layer;

[0009] Finally, in the Fe 2 AB 2 A metallization layer may be prepared on the surface of the transition layer;

[0010] The metallization layer is an Ag and / or Cu layer.

[0011] Furthermore, the chemical structure formula of the PZT high frequency ceramic is as follows:

[0012] Pb(Zr 1 / 2 Ti 1 / 2 ) 3 -xwt%Ln 2 O 3

[0013] Among them, Ln2 O 3 It is a lanthanide rare earth element oxide, 0.1≤x≤1.

[0014] Furthermore, Ln 2 O 3 For Dy 2 O 3 .

[0015] Further, x=0.8.

[0016] Furthermore, the preparation method of the PZT high frequency ceramic is as follows:

[0017] Pb 3 O 4 、ZrO 2 、TiO 2 , Ln 2 O 3 The mixture is ball-milled and dried, and pre-fired at 800-850°C for 1-5h. The pre-fired product is ball-milled again and dried, a binder is added to granulate, and the mixture is pressed and heated to remove the binder, and finally sintered at 1250-1300°C for 1-5h.

[0018] Furthermore, the Fe 2 AB 2 The preparation method of the transition layer is as follows:

[0019] Place the PZT high-frequency ceramic in a quartz boat, and then place the quartz boat in the center of the heating area of ​​the tube furnace. Then introduce a hydrogen-argon mixed gas, and heat the tube furnace to 1000-1150°C under the protection of this atmosphere. Introduce ferric chloride gas, aluminum chloride gas and boron chloride gas into the tube furnace to react for 10-60 minutes. After the reaction is terminated, cool naturally to room temperature.

[0020] Furthermore, the volume ratio of hydrogen to argon in the hydrogen-argon mixed gas is 1-5:1-5.

[0021] Furthermore, the metallization layer is prepared by a magnetron sputtering method.

[0022] Beneficial effects of the present invention:

[0023] The present invention provides a method for metallizing the surface of a PZT high-frequency ceramic. 2 AB 2The transition layer is in the transition zone from typical metal to typical ceramic, and its performance is also between the two, which effectively bridges the property gap between metal and ceramic, can effectively promote the bonding between PZT high-frequency ceramic and metallization layer, and effectively alleviate the thermal stress caused by the large difference in the properties of the two materials near the interface, and improve the bonding strength between the metallization layer and the PZT high-frequency ceramic. In the prior art, rare earth elements have played a positive role in improving the piezoelectric properties of PZT ceramics. The present application further finds that lanthanide rare earth element oxides in PZT high-frequency ceramics also have a certain degree of improvement effect on the bonding strength of the metallization layer. The reason may be that the lanthanide rare earth elements play an interface effect and improve the Fe 2 AB 2 The microstructure between the transition layer and the PZT high-frequency ceramic interface makes Fe 2 AB 2 The transition layer is tightly bonded to the surface of the PZT high frequency ceramic, thereby increasing the bonding strength of the metallization layer to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Fe prepared in Example 1-4 2 AB 2 XRD pattern of the transition layer. DETAILED DESCRIPTION

[0025] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0026] Embodiment 1:

[0027] This embodiment provides a PZT high-frequency ceramic surface metallization method:

[0028] Pb 3 O 4 、ZrO 2 、TiO 2 、Dy 2 O 3The mixture was added to a ball mill, and anhydrous ethanol was used as a ball milling medium. The mixture was mixed and ball milled in a planetary ball mill for 10 hours, dried, and then heated to 850°C for pre-sintering for 2 hours. The pre-sintered product was added to a ball mill, and anhydrous ethanol was used as a ball milling medium. The mixture was ball milled again in a planetary ball mill for 10 hours and dried. A polyvinyl alcohol aqueous solution with a mass concentration of 8wt% was added as a binder and granulated. The obtained granules were added to a mold and pressed at 100MPa to obtain a green body. The green body was heated to 650°C at a rate of 1°C / min and kept for debinding for 2 hours. Finally, the temperature was raised to 1250°C at a rate of 10°C / min and sintered for 2 hours to obtain PZT high-frequency ceramics. The general chemical structure of PZT high-frequency ceramics is Pb(Zr 1 / 2 Ti 1 / 2 ) 3 -0.8wt%Dy 2 O 3 ;

[0029] The above-mentioned PZT high-frequency ceramic was placed in a quartz boat, and then the quartz boat was placed in the center of the heating area of ​​the tube furnace, and then a hydrogen-argon mixed gas was introduced, in which the volume ratio of hydrogen to argon was 1:1. Under the protection of this atmosphere, the tube furnace was heated to 1100°C, and ferric chloride gas, aluminum chloride gas and boron chloride gas were introduced into the tube furnace from different pipes for reaction for 30 minutes, and the molar ratio of the ferric chloride gas, aluminum chloride gas and boron chloride gas introduced was 2:1:2. After the reaction was terminated, it was naturally cooled to room temperature to obtain a transition layer with a thickness of 1 μm. The transition layer was sampled for X-ray diffraction (XRD) test, and the phase composition of the analysis material was pure phase Fe 2 AB 2 ;

[0030] The PZT high-frequency ceramic with the transition layer deposited on the surface was clamped at both ends by the loading fixture of the magnetron sputtering coating machine. Pure silver was used as the target material. When the vacuum degree of the coating machine studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering pure silver target is 10A, the time is 20min, after the single-sided sputtering is completed, the loading fixture is turned over, and the silver layer is sputtered on the other side with the same sputtering conditions, and the thickness of the silver layer is 1.5μm.

[0031] The tensile strength of the silver layer was measured to be 19.5 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0032] Embodiment 2:

[0033] This embodiment provides a PZT high-frequency ceramic surface metallization method:

[0034] Pb 3 O 4 、ZrO2 、TiO 2 Dy 2 O 3 The mixture was added to a ball mill, and anhydrous ethanol was used as a ball milling medium. The mixture was mixed and ball milled in a planetary ball mill for 10 hours, dried, and then heated to 850°C for pre-sintering for 2 hours. The pre-sintered product was added to a ball mill, and anhydrous ethanol was used as a ball milling medium. The mixture was ball milled again in a planetary ball mill for 10 hours and dried. A polyvinyl alcohol aqueous solution with a mass concentration of 8wt% was added as a binder and granulated. The obtained granules were added to a mold and pressed at 100MPa to obtain a green body. The green body was heated to 650°C at a rate of 1°C / min and kept for debinding for 2 hours. Finally, the temperature was raised to 1250°C at a rate of 10°C / min and sintered for 2 hours to obtain PZT high-frequency ceramics. The general chemical structure of PZT high-frequency ceramics is Pb(Zr 1 / 2 Ti 1 / 2 ) 3 -0.8wt%Dy 2 O 3 ;

[0035] The above-mentioned PZT high-frequency ceramic was placed in a quartz boat, and then the quartz boat was placed in the center of the heating area of ​​the tube furnace, and then a hydrogen-argon mixed gas was introduced, in which the volume ratio of hydrogen to argon was 1:1. Under the protection of this atmosphere, the tube furnace was heated to 1050°C, and ferric chloride gas, aluminum chloride gas and boron chloride gas were introduced into the tube furnace from different pipes for reaction for 30 minutes, and the molar ratio of the ferric chloride gas, aluminum chloride gas and boron chloride gas introduced was 2:1:2. After the reaction was terminated, it was naturally cooled to room temperature to obtain a transition layer with a thickness of 1 μm. The transition layer was sampled for X-ray diffraction (XRD) test and the analytical phase composition was pure phase Fe 2 AB 2 ;

[0036] The PZT high-frequency ceramic with the transition layer deposited on the surface was clamped at both ends by the loading fixture of the magnetron sputtering coating machine. Pure silver was used as the target material. When the vacuum degree of the coating machine studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering pure silver target is 10A, the time is 20min, after the single-sided sputtering is completed, the loading fixture is turned over, and the silver layer is sputtered on the other side with the same sputtering conditions, and the thickness of the silver layer is 1.5μm.

[0037] The tensile strength of the silver layer was measured to be 18.9 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0038] Embodiment 3:

[0039] This embodiment provides a PZT high-frequency ceramic surface metallization method:

[0040] Pb 3 O 4 、ZrO 2 、TiO 2 、Dy 2 O 3 The mixture was added to a ball mill, and anhydrous ethanol was used as a ball milling medium. The mixture was mixed and ball milled in a planetary ball mill for 10 hours, dried, and then heated to 850°C for pre-sintering for 2 hours. The pre-sintered product was added to a ball mill, and anhydrous ethanol was used as a ball milling medium. The mixture was ball milled again in a planetary ball mill for 10 hours and dried. A polyvinyl alcohol aqueous solution with a mass concentration of 8wt% was added as a binder and granulated. The obtained granules were added to a mold and pressed at 100MPa to obtain a green body. The green body was heated to 650°C at a rate of 1°C / min and kept for debinding for 2 hours. Finally, the temperature was raised to 1250°C at a rate of 10°C / min and sintered for 2 hours to obtain PZT high-frequency ceramics. The general chemical structure of PZT high-frequency ceramics is Pb(Zr 1 / 2 Ti 1 / 2 ) 3 -0.8wt%Dy 2 O 3 ;

[0041] The above-mentioned PZT high-frequency ceramic was placed in a quartz boat, and then the quartz boat was placed in the center of the heating area of ​​the tube furnace, and then a hydrogen-argon mixed gas was introduced, in which the volume ratio of hydrogen to argon was 1:1. Under the protection of this atmosphere, the tube furnace was heated to 1000°C, and ferric chloride gas, aluminum chloride gas and boron chloride gas were introduced into the tube furnace from different pipes for reaction for 30 minutes, and the molar ratio of the ferric chloride gas, aluminum chloride gas and boron chloride gas introduced was 2:1:2. After the reaction was terminated, it was naturally cooled to room temperature to obtain a transition layer with a thickness of 1 μm. The transition layer was sampled for X-ray diffraction (XRD) test and the analytical phase composition was pure phase Fe 2 AB 2 ;

[0042] The PZT high-frequency ceramic with the transition layer deposited on the surface was clamped at both ends by the loading fixture of the magnetron sputtering coating machine. Pure silver was used as the target material. When the vacuum degree of the coating machine studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering pure silver target is 10A, the time is 20min, after the single-sided sputtering is completed, the loading fixture is turned over, and the silver layer is sputtered on the other side with the same sputtering conditions, and the thickness of the silver layer is 1.5μm.

[0043] The tensile strength of the silver layer was measured to be 18.2 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0044] Embodiment 4:

[0045] This embodiment provides a PZT high-frequency ceramic surface metallization method:

[0046] Pb 3 O 4 、ZrO 2 、TiO 2 、Dy 2 O 3 The mixture was added to a ball mill, and anhydrous ethanol was used as a ball milling medium. The mixture was mixed and ball milled in a planetary ball mill for 10 hours, dried, and then heated to 850°C for pre-sintering for 2 hours. The pre-sintered product was added to a ball mill, and anhydrous ethanol was used as a ball milling medium. The mixture was ball milled again in a planetary ball mill for 10 hours and dried. A polyvinyl alcohol aqueous solution with a mass concentration of 8wt% was added as a binder and granulated. The obtained granules were added to a mold and pressed at 100MPa to obtain a green body. The green body was heated to 650°C at a rate of 1°C / min and kept for debinding for 2 hours. Finally, the temperature was raised to 1250°C at a rate of 10°C / min and sintered for 2 hours to obtain PZT high-frequency ceramics. The general chemical structure of PZT high-frequency ceramics is Pb(Zr 1 / 2 Ti 1 / 2 ) 3 -0.8wt%Dy 2 O 3 ;

[0047] The above-mentioned PZT high-frequency ceramic was placed in a quartz boat, and then the quartz boat was placed in the center of the heating area of ​​the tube furnace, and then a hydrogen-argon mixed gas was introduced, in which the volume ratio of hydrogen to argon was 1:1. Under the protection of this atmosphere, the tube furnace was heated to 1150°C, and ferric chloride gas, aluminum chloride gas and boron chloride gas were introduced into the tube furnace from different pipes for reaction for 30 minutes, and the molar ratio of the ferric chloride gas, aluminum chloride gas and boron chloride gas introduced was 2:1:2. After the reaction was terminated, it was naturally cooled to room temperature to obtain a transition layer with a thickness of 1 μm. The transition layer was sampled for X-ray diffraction (XRD) test, and the phase composition of the analysis material was pure phase Fe 2 AB 2 ;

[0048] The PZT high-frequency ceramic with the transition layer deposited on the surface was clamped at both ends by the loading fixture of the magnetron sputtering coating machine. Pure silver was used as the target material. When the vacuum degree of the coating machine studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering pure silver target is 10A, the time is 20min, after the single-sided sputtering is completed, the loading fixture is turned over, and the silver layer is sputtered on the other side with the same sputtering conditions, and the thickness of the silver layer is 1.5μm.

[0049] The tensile strength of the silver layer was measured to be 19.3 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0050] Comparative Example 1:

[0051] It is basically the same as Example 1, except that no transition layer is deposited on the surface of the PZT high-frequency ceramic, but silver is directly plated.

[0052] This comparative example provides a PZT high-frequency ceramic surface metallization method:

[0053] Pb 3 O 4 、ZrO 2 、TiO 2 、Dy 2 O 3 The mixture was added to a ball mill, and anhydrous ethanol was used as a ball milling medium. The mixture was mixed and ball milled in a planetary ball mill for 10 hours, dried, and then heated to 850°C for pre-sintering for 2 hours. The pre-sintered product was added to a ball mill, and anhydrous ethanol was used as a ball milling medium. The mixture was ball milled again in a planetary ball mill for 10 hours and dried. A polyvinyl alcohol aqueous solution with a mass concentration of 8wt% was added as a binder and granulated. The obtained granules were added to a mold and pressed at 100MPa to obtain a green body. The green body was heated to 650°C at a rate of 1°C / min and kept for debinding for 2 hours. Finally, the temperature was raised to 1250°C at a rate of 10°C / min and sintered for 2 hours to obtain PZT high-frequency ceramics. The general chemical structure of PZT high-frequency ceramics is Pb(Zr 1 / 2 Ti 1 / 2 ) 3 -0.8wt%Dy 2 O 3 ;

[0054] The two ends of the PZT high-frequency ceramic were clamped by the loading fixture of the magnetron sputtering coating machine, and pure silver was used as the target material. When the vacuum degree of the coating machine studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering pure silver target is 10A, the time is 20min, after the single-sided sputtering is completed, the loading fixture is turned over, and the silver layer is sputtered on the other side with the same sputtering conditions, and the thickness of the silver layer is 1.5μm.

[0055] The tensile strength of the silver layer was measured to be 13.3 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0056] Comparative Example 2:

[0057] The same as Example 1, except that the composition of the PZT high frequency ceramic does not contain Dy 2 O 3 .

[0058] This comparative example provides a PZT high-frequency ceramic surface metallization method:

[0059] Pb 3 O 4 、ZrO 2 、TiO 2 、MnCO 3 , Nb 2 O 5 The mixture was added to a ball mill, and anhydrous ethanol was used as a ball milling medium. The mixture was mixed and ball milled in a planetary ball mill for 10 hours, dried, and then heated to 850°C for pre-sintering for 2 hours. The pre-sintered product was added to a ball mill, and anhydrous ethanol was used as a ball milling medium. The mixture was ball milled again in a planetary ball mill for 10 hours and dried. A polyvinyl alcohol aqueous solution with a mass concentration of 8wt% was added as a binder and granulated. The obtained granules were added to a mold and pressed at 100MPa to obtain a green body. The green body was heated to 650°C at a rate of 1°C / min and kept for debinding for 2 hours. Finally, the temperature was raised to 1250°C at a rate of 10°C / min and sintered for 2 hours to obtain PZT high-frequency ceramics. The general chemical structure of PZT high-frequency ceramics is Pb(Zr 1 / 2 Ti 1 / 2 ) 3 ;

[0060] The PZT high-frequency ceramic is placed in a quartz boat, and the quartz boat is placed in the center of the heating area of ​​a tube furnace, and then a hydrogen-argon mixed gas is introduced, wherein the volume ratio of hydrogen to argon in the hydrogen-argon mixed gas is 1:1, and the tube furnace is heated to 1100°C under the protection of the atmosphere, and ferric chloride gas, aluminum chloride gas and boron chloride gas are introduced into the tube furnace from different pipes for reaction for 30 minutes, wherein the molar ratio of the introduced ferric chloride gas, aluminum chloride gas and boron chloride gas is 2:1:2, and after the reaction is terminated, the mixture is naturally cooled to room temperature to obtain a transition layer with a thickness of 1 μm;

[0061] The PZT high-frequency ceramic with the transition layer deposited on the surface was clamped at both ends by the loading fixture of the magnetron sputtering coating machine. Pure silver was used as the target material. When the vacuum degree of the coating machine studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering pure silver target is 10A, the time is 20min, after the single-sided sputtering is completed, the loading fixture is turned over, and the silver layer is sputtered on the other side with the same sputtering conditions, and the thickness of the silver layer is 1.5μm.

[0062] The tensile strength of the silver layer was measured to be 17.4 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0063] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for metallizing the surface of PZT high-frequency ceramics, characterized in that: The details are as follows: First, prepare PZT high-frequency ceramics; Preparing a Fe2AlB2 transition layer on the surface of the PZT high frequency ceramic; Finally, a metallization layer is prepared on the surface of the Fe2AlB2 transition layer; The metallization layer is an Ag and / or Cu layer.

2. The PZT high frequency ceramic surface metallization method according to claim 1, characterized in that: The chemical structure formula of the PZT high frequency ceramic is as follows: <h2 style=";text-align:left;direction:ltr">Pb(Zr<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> )O3-xwt%Ln2O3 Among them, Ln2O3 is a lanthanide rare earth element oxide, 0.1≤x≤1.

3. The PZT high frequency ceramic surface metallization method according to claim 2, characterized in that: Ln2O3 is Dy2O3.

4. The PZT high frequency ceramic surface metallization method according to claim 2, characterized in that: x=0.8。 5. The PZT high frequency ceramic surface metallization method according to claim 2, characterized in that: The preparation method of the PZT high frequency ceramic is as follows: Pb3O4, ZrO2, TiO2 and Ln2O3 are mixed and ball-milled, dried and pre-calcined at 800-850°C for 1-5h. The pre-calcined product is ball-milled again and dried, a binder is added to granulate, pressed into shape, heated to remove binder, and finally sintered at 1250-1300°C for 1-5h.

6. The PZT high frequency ceramic surface metallization method according to claim 1, characterized in that: The preparation method of the Fe2AlB2 transition layer is as follows: Place the PZT high-frequency ceramic in a quartz boat, and then place the quartz boat in the center of the heating area of ​​the tube furnace. Then introduce a hydrogen-argon mixed gas, and heat the tube furnace to 1000-1150°C under the protection of this atmosphere. Introduce ferric chloride gas, aluminum chloride gas and boron chloride gas into the tube furnace to react for 10-60 minutes. After the reaction is terminated, cool naturally to room temperature.

7. The PZT high frequency ceramic surface metallization method according to claim 6, characterized in that: The volume ratio of hydrogen to argon in the hydrogen-argon mixed gas is 1-5:1-5.

8. The PZT high frequency ceramic surface metallization method according to claim 1, characterized in that: The metallization layer is prepared by a magnetron sputtering method.

Citation Information

Patent Citations

  • MAB phase ceramic-metal layered composite material as well as preparation method and application thereof

    CN111873570A

  • Laminated type magnetic head

    JP1995153017A